Advances in Food Processing based on Sustainable Bioeconomy - SAMILYK, Maryna; LUKASH, Svitlana; BOLGOVA, Natalia; HELIKH, Anna; MASLAK, Nataliia; MASLAK, Oleksandr (Journal of Environmental Management and Tourism, 2020)
Bio economics can use a range of raw materials and use various processes to transform these raw materials into a wide range of different products. Examples of a wide range of commodities, products and processes are given. The present study focuses on developed countries to propose some marketing actions that could help in reducing food waste. The main contribution of this study is the proposal of marketing actions that help in tacking food waste, as one of the main perspective approaches in bioeconomy. The benefits of vegetable and fruit processing in the context of bio economics are generalized. Based on the analysis, a model of waste-free technologies was developed. Considering the advantages of applying the principle of non-waste production, the author's technology of integrated processing of vegetables was developed, taking into account the improvement of existing methods. The main advantages of the proposed method of non-waste processing of vegetables directed to the sustainable consumption identified in the areas: social, economic and natural.